THE INFLUENCE OF ONLINE VIDEO CONTENT ON TIKTOK SHOP CONSUMER BEHAVIOR - Dendi, Dendi; Ramanda, Ramanda; Firmansyah, Wahyu Ridho (Journal of Public Relations and Digital Communication (JPRDC), 2023)
This research aims to analyze the influence of online video content on consumer behavior in the Tik Tok Shop context. With the increasing popularity of Tik Tok as a social media platform focused on video content, the question of how video content influences consumer behavior has become relevant. The research results show that there is a significant correlation between online video content presented on Tik Tok Shop and consumer online shopping behavior. Interesting, informative and creative video content tends to increase consumer interest in purchasing the product or service being promoted. In addition, this research also identified that Tik Tok's special features, such as duets, challenges, and live streaming, have a significant impact in increasing consumer engagement. Utilization of these features by sellers can increase interactions with consumers, which in turn can influence purchasing decisions. In conclusion, online video content has an important role in shaping consumer behavior at Tik Tok Shop. Therefore, sellers and marketers need to understand the importance of creating engaging and creative content to achieve their marketing goals on these platforms.